Assessing the Impact of Corporate Sustainability Practices in Enhancing Organizational Growth in the Insurance Industry in Cameroon - Mukem, Abe Simon (Digital Repository of Theses, 2026)
This research workassessed the impact of corporate sustainability practices in fostering organizational growth in the Cameroonian insurance sector. The purpose of theresearchhinges on systematically investigating the effect of corporate sustainability practices in the Cameroon insurance landscape and how those endeavours can influence company growth or performance when implemented and challenges encountered during implementation. 15 insurance companies and one reinsurance company were sampled out of our targeted sample of 12 -14 companies. A total of 54 respondents, with 27 from the life insurance branch, 19 from the non-life branch and 8 who did not specify their branch of insurance, were obtained. Data gathering was carried out through the use of questionnaires administered to personnel of sampled insurance carriers as well as semi-structured interviews administered to senior executive staff of the sampled insurance companies, including sustainability and strategy officers. The results indicated that several sustainability initiatives exhibit statistically significant relationships with perceived market share influence. Notably, stakeholder engagement emerged as a strong positive predictor, indicating that firms that actively involve stakeholders in sustainability efforts are significantly more likely to report a higher influence of these strategies on market share. Similarly, improved operational excellence and easy access to financing are positively associated with market share influence. These findings suggest that when sustainability practices are integrated with operational efficiency and financial accessibility, they are more likely to yield competitive advantages. Other predictors such as reduced carbon footprint and corporate social responsibility (CSR) initiatives are also positively and significantly associated with increased market share influence. Additionally, honesty and transparency in business practices contributes positively to perceived market gains, reinforcing the importance of ethical communication and accountability in sustainability messaging. Interestingly, the analysis revealed that some sustainability practices are negatively associated with market share influence. For instance, recycling and waste reduction and worker wellness programs show significant negative coefficients. This suggests that although these practices may be important from an environmental or social standpoint, they may not directly translate into perceived market share gains. Furthermore, ethical decision-making and image and brand improvement are also negatively related to market share influence. Financial constraints and lack of reliable data indicators were among the major impediments to sustainability implementation. From the results, further research is recommended, as the study relied to a greater extent on self-reported data, that could cause prejudice. In addition,thefocus of the research was limited to the insurance sector, and Cameroon, making the results difficult to fully generalise. Keywords: Sustainability, Corporate Sustainability, Growth, Insurance industry